Enhancing interlayer bonding in concrete 3D printing applications - Lim, Darryl Wi Chung (2019)
Concrete 3D printing has been garnering much interest in the construction and civil engineering world lately. Much effort has been put into the research on producing the best concrete mixture suitable for printing. The material must be able to flow in order to be extruded by the printer but also recover and set fast enough with sufficient strength to support the weight of the subsequent layers deposited upon it. The bond between deposited layers have to be strong as well so that the structure does not collapse easily even after setting. Adding admixtures is a way to modify the properties of cement to make it suitable for printing as well as viable for building strong structures with strong interlayer bonding. Rheological tests were performed for various samples containing cement pastes with different admixtures. Next, the mixtures with the most potential were chosen for 3D printing. Finally, tensile splitting tests were done on the printed samples to get an indication of the strength of the bond between layers and the results were then compared and evaluated.